DIFFERENTIATION OF CA1 CELL ELEMENTS IN RAT HIPPOCAMPUS ONTOGENESIS - Brichova, Hana (Biomedical papers, 2004)
Development of cell elements of CA1, their interaction in the process of cell differentiation during hippocampal band formation, developed CA1, and changes in the ageing process are discussed.
Keywords: Hippocampal formation/Neuroepithelium/Neuroblast/Glioblast/Apoptosis/Neuron/Astrocyte/Microglia/Oligodendrocyte/